PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR MATERI SISTEM EKSRESI PADA MANUSIA PADA SISWA KELAS VIII SMPN 2 RAMAN UTARA - Dian Indriyani; HRA Mulyani; Hening Widowati (EDUBIOLOCK, 2023)
This study aimed to determine the effect of guided discovery learning on the critical thinking skills of students in class VIII Science in SMP N 2 Raman Utara. This type of research is experimental with a design using Posttest Only Control, Researchers use instruments in the form of essay test items (descriptions) that are used by researchers to measure students’ abilities after carrying out the learning process using a guided Discovery Learning. Researchers used 2 groups with research design, namely the control group using the Direct Learning model with the question and answer method and the experimental group using guided Discovery Learning with the group discussion method. The research data is tested for hypotheses with the similarity test of two averages. The test results with the normality test show = 9,93 > X2daf = 11,07 α = 0.05, then, in the similarity test two t-count average > t-daf is 17,9 < 2,01 (= 5%). So there is an influence of guided Discovery Learning on students' critical thinking skills at SMP N 2 Raman Utara.